Evolution of energy and the transformation of man in Russian and foreign utopias - A. V. Grigorovskaya (Шаги, 2024)
The article analyzes the relationships between the sources of energy and of human culture in Russian and foreign utopias. The author considers the main way of correlation between the evolution of energy and anthropological evolution, which involves their mutual influence. Utopian texts demonstrate this interdependence quite clearly. Technological stagnation is combined with the totalitarian structure of society in the early utopias: in texts by Plato, Thomas More, Tommaso Campanella (in Francis Bacon’s utopia it is the pursuit of modernization). Bacon’s model is reproduced in the novel Andromeda Nebula by the Soviet writer Ivan Yefremov, however, the discovery and the implementation of innovative energy sources in this utopia is accompanied by a qualitative change of human beings and society. In Ayn Randʼs novel Atlas Shrugged the motif of the “perpetuum mobile” is organically combined with the motif of human transformation. Nikolai Chernyshevsky also wrote about the “perpetuum mobile”: in his stories he emphasized the inextricable link between “energy” and “anthropology”. Analysis of current trends in the development of this topic (as seen, for example, in Kim Stanley Robinsonʼs novel The Ministry for the Future) allows us to conclude that totalitarian narratives in utopia are being revived. These totalitarian narratives impose on humankind the inevitability of rapid energy transition.